Experiências de sofrimento psíquico na adolescência - Nied, Camila (Universidade do Vale do Rio dos Sinos, 2025)
This doctoral thesis, developed within the Graduate Program in Public Health at the University of Vale do Rio dos Sinos (UNISINOS), focused on the experiences of psychological suffering among adolescents. The research aimed to understand how adolescents experience psychological suffering and the meaning of their actions in the life-world, grounded in the sociological phenomenology of Alfred Schutz. The qualitative study was conducted in a public school in Rio Grande do Sul, Brazil, through individual interviews with 20 students aged 16 to 19, carried out in 2023. The analysis interpreted adolescents’ experiences through concepts such as biographical situation, stock of knowledge, motivations, and typifications. The project was approved by the Research Ethics Committee of UNISINOS under opinion number 6.186.778. The results unfold into two articles: the first discusses adolescents’ motivations for work — a theme that emerged significantly during interviews and analysis — while the second focuses on experiences of psychological suffering and the meaning of action in the face of such experiences. Findings from the first article revealed that adolescent work, although marked by challenges, is understood by adolescents as a possibility for autonomy, belonging, and social recognition, thus constituting a situated social action shaped by multiple motivations. The second article showed that psychological suffering mainly arises from fragile family and school relationships and is expressed through “unspeakability,” often silenced or trivialized by others. The actions mobilized in response to these experiences ranged from silence and self-injury to seeking support and developing personal ways of resignification. The convergence of the thesis findings demonstrates that adolescence should be understood as an experience situated in the life-world, rather than merely as a normative stage of development, recognizing adolescents as subjects of social action. By problematizing phenomena often treated in normative or pathologizing ways, this thesis contributes to broadening the debate on adolescence and mental health in the field of Public Health, offering insights for future research, public policies, and care practices that value adolescents’ uniqueness, strengthen qualified listening, and expand intersectoral support networks.
Keywords: Saúde mental; Adolescentes; Fenomenologia; Mental health; Adolescents; Phenomenology; ACCNPQ::Ciências da Saúde::Saúde Coletiva